Can Insurance Companies Use My AI Health Data? Navigating the Legal and Ethical Maze - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare has ushered in an era of unprecedented diagnostic and treatment capabilities. From wearable dev...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Wearable Technology